US-China rivalry: managing a deep and wide gulf - Han, Fook Kwang (2024)
US-China relations are looking better than they were a year ago, but the gulf remains deep, wide and probably long-lasting on most of the important issues between the two great powers. Both sides know this and do not expect much progress. In this new reality, the rest of the world needs to adjust its expectations about what can be achieved.